2019
DOI: 10.1177/1758835919838958
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of long noncoding RNA LINC01419 in esophageal squamous cell carcinoma and its relation to the sensitivity to 5-fluorouracil by mediating GSTP1 methylation

Abstract: Background: Genome-wide sequencing investigations have identified numerous long noncoding RNAs (lncRNAs) among mammals, many of which exhibit aberrant expression in cancers, including esophageal squamous cell carcinoma (ESCC). Herein, this study elucidates the role and mechanism by which LINC01419 regulates the DNA methylation of glutathione S-transferase pi 1 (GSTP1) in relation to ESCC progression and the sensitivity of ESCC cells to 5-fluorouracil (5-FU). Methods: LI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…In ESCC, ncRNAs have been suggested to play roles as oncogenes or tumor suppressors to regulate ESCC proliferation, apoptosis, epithelial-mesenchymal transition (EMT), metastasis, chemotherapy, or radiotherapy [33][34][35][36][37]. Additionally, several ncRNAs have been observed to serve as prognostic markers in patients with ESCC [5,38]. Several studies which suggest the role and mechanism of ncRNAs in the development of ESCC have been summarized in Table 1.…”
Section: Role Of Non-coding Rnas In Escc Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ESCC, ncRNAs have been suggested to play roles as oncogenes or tumor suppressors to regulate ESCC proliferation, apoptosis, epithelial-mesenchymal transition (EMT), metastasis, chemotherapy, or radiotherapy [33][34][35][36][37]. Additionally, several ncRNAs have been observed to serve as prognostic markers in patients with ESCC [5,38]. Several studies which suggest the role and mechanism of ncRNAs in the development of ESCC have been summarized in Table 1.…”
Section: Role Of Non-coding Rnas In Escc Progressionmentioning
confidence: 99%
“…Chemotherapy, radio-chemotherapy, and esophagectomy are the predominant therapeutic strategies for ESCC. However, the 5-year survival rate is still poor (<15%) [5,6]. Thus, it is of high importance to understand the pathogenetic mechanisms of ESCC and develop effective strategies to treat ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia is one of the important hallmarks of tumor microenvironment. Increasing studies have revealed that tumor hypoxia is closely related to the progression of cancer, such as tumor metastasis, recurrence and drug resistance [23][24][25][26]. It has been confirmed that hypoxia in vivo is associated with poor prognosis and high mortality in ovarian cancer patients, and involved in ovarian cancer cell proliferation [27,28].…”
Section: Discussionmentioning
confidence: 96%
“…Hypoxia is one of the important hallmarks of tumor microenvironment. Increasing studies have revealed that tumor hypoxia is closely related to the progression of cancer, such as tumor metastasis, recurrence and drug resistance [25][26][27][28]. It has been con rmed that hypoxia in vivo is associated with poor prognosis and high mortality in ovarian cancer patients, and involved in ovarian cancer cell proliferation [29,30].…”
Section: Discussionmentioning
confidence: 99%